The effects of technology investment on financial stability: Evidence from commercial banks in Vietnam - Nhat, Nguyen Minh (The Economics and Finance Letters, 2025)
This study examines the effects of technology investments on financial stability at commercial banks in Vietnam. Financial services provided by banks are vital to the growth and development of the Vietnamese economy. Due to competitive constraints and the need to keep up with fast-moving FinTech startups, Vietnamese banks have made digital transformation a top strategic goal. Therefore, the study aims to investigate the impact of technology investment on the financial stability of commercial banks in Vietnam from 2012 to 2023. The research used financial data from 26 joint-stock commercial banks and panel data analysis with the ordinary least squares (OLS), fixed effect model (FEM), random effects model (REM), and generalized method of moments (GMM) to look into the link between bank stability and technology spending. The findings reveal that while technology investment significantly enhances operational efficiency and market competitiveness, it poses risks, particularly during the initial stages of digital transformation. The results show a significant negative effect of technology investment on financial stability, highlighting the need for strategic planning and robust regulatory frameworks. These insights provide valuable recommendations for bank management and policymakers to balance technological advancements with financial stability, especially in economic disruptions like the COVID-19 pandemic. Finally, the practical implications help commercial banks strive to increase asset size and expand operations to strengthen financial capacity, increase brand recognition, create solid customer trust, improve competitiveness, and bring high profits.